Penyelesaian Sengketa Perdata-Pidana dalam Kasus Penipuan Berbasis Investasi Bodong - Aris, Umar; Dewanto, Wishnu; Hasan, Bob (Neolectura, 2025)
Investment fraud, commonly referred to as investasi bodong, has become a major issue in Indonesia, causing significant financial losses and weakening public confidence in the financial sector. The rapid growth of digital technology has expanded and complicated fraudulent schemes, posing new challenges for law enforcement and regulatory institutions. This study aims to analyze civil and criminal dispute resolution mechanisms in investment fraud cases, assess their effectiveness, and identify key challenges and reforms needed. Using a qualitative approach within a normative legal framework, the research examines relevant laws—including the Criminal Code, Civil Code, ITE Law, Capital Market Law, Banking Law, Consumer Protection Law, Anti-Money Laundering Law, and OJK regulations—supported by secondary data and case studies. Findings reveal that, despite established legal frameworks, practical enforcement remains weak due to complex digital evidence, jurisdictional barriers, and limited resources. A holistic reform integrating regulatory adaptation, institutional coordination, and digital literacy is urgently required.